Multimedia system for integrated reading acceleration and assistance (SMAART) in literacy learning in high school - Afiati, Laksmita Nur; Rianto, Rianto; Damaianti, Vismaia S.; Mulyaningsih, Indrya (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
This study aimed to develop the Multimedia System for Accelerated and Assisted Integrated Reading (SMAART), an interactive learning application specifically designed to support high school students with literacy disabilities. Utilizing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, the study only reached the development stage. This study followed a systematic development process to ensure the application's pedagogical and technical effectiveness. The analysis phase identified key literacy challenges through teacher interviews and student observations, while the design phase incorporated multimedia principles to create an engaging and accessible interface. During development, the application was built using Articulate Storyline 3, integrating text, audio, and visual elements to accommodate diverse learning needs. Expert validation was conducted with media specialists (assessing usability and design) and literacy educators (evaluating content relevance), resulting in high scores for display quality (4.6/5) and instructional effectiveness (4.4/5). User feedback highlighted the application's intuitive navigation (89% satisfaction rate), interactive exercises, and motivational multimedia components. The evaluation phase confirmed the effectiveness of SMAART as a complementary tool for literacy education, especially for students with learning disabilities. Its success underscores the potential of adaptive multimedia technology to promote inclusive education. Future research could expand testing to broader demographics and explore AI-based personalization. Ultimately, SMAART offers a scalable model for digital literacy interventions, aligning with the School Literacy Movement (GLS) initiative in Indonesia and addressing the gap in accessible learning resources for students with disabilities.